Anteseden Profitabilitas Bank BUMN di Indonesia - Andry Priharta; Darto Darto; Nur Asni Gani; Jaharuddin Jaharuddin (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2022)
The purpose of this study is to prove empirically whether capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, Net Interest Margin and Company Size affect the profitability of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the period 2011-2020. The method in this study is regression analysis of panel data. The population in this study is all state-owned bank companies listed on the Indonesia Stock Exchange (IDX) for the period 2011-2020. Selection of samples by purposive sampling method, selected research samples as many as 4 state-owned bank companies. The data analysis technique in this study is regression of panel data using annual data. The results of the F test study showed all independent variables namely Capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, Net Interest Margin and Company Size significantly affect profitability. The results of the t test found that variable Capital Adequacy Ratio and Loan to Deposit Ratio negatively had no significant effect on profitability. Non-Performing Loans negatively and significantly affect profitability. Net Interest Margin has a positive and significant effect on profitability. While the company's size variables have a positive effect on profitability. Keywords: Capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, Net Interest Margin, SIZE, State-Owned Banks